2017
DOI: 10.13057/biodiv/d180320
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Tor douronensis (Pisces: Cyprinidae) in West Sumatra, Indonesia

Abstract: Abstract. Roesma DI, Tjong DH, Munir W, Agesi AV, Chornelia A. 2017. Genetic diversity of Tor douronensis (Pisces: Cyprinidae) in West Sumatra, Indonesia. Biodiversitas 18: 1018-1025. A random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) analysis was applied to determine the genetic diversity within and among the populations of Tor douronensis in West Sumatra river system. The results provided information for proper breeding, maintenance, and conservation of T. douronensis. The highest and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…This also proved by the results of the research which reported that there are variations in the number of fish species found in 11 tributaries of Batang Toru (North Sumatra) as the main river [35]. It also reported that there is genetic variation intra and inter populations of Tor douronensis (Cyprinidae) from 21 rivers in West Sumatra [36]. Based on our study in Sumatra fishes, we considered that it is essential to combine the morphological data and molecular data in taxa grouping.…”
Section: Resultsmentioning
confidence: 63%
“…This also proved by the results of the research which reported that there are variations in the number of fish species found in 11 tributaries of Batang Toru (North Sumatra) as the main river [35]. It also reported that there is genetic variation intra and inter populations of Tor douronensis (Cyprinidae) from 21 rivers in West Sumatra [36]. Based on our study in Sumatra fishes, we considered that it is essential to combine the morphological data and molecular data in taxa grouping.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, a study in the Kreuang Sabee River, Aceh Jaya District, Indonesia showed only T. tambra [ 78 ]. Although T. douronensis has been classified as an invalid species, this species has been widely studied in Indonesia and found widely distributed in several rivers on Sumatra, namely Batang Gumanti River, Batang Antokan River, Batang Malalo River, Batang Matur River, Batang Sinuruik River, and Lubuk Mangkuih River [ 79 ].…”
Section: Geographical Distribution Of Tor Species In the Se Asian Regionmentioning
confidence: 99%
“…The fish diversity studies in Sumatra, especially in West Sumatra, Indonesia using the conventional method with direct organism capture has been undertaken for studying fish diversity in West Sumatra Lake (Roesma 2011) and Batang Toru river system (Roesma et al 2016), genetic diversity of Tor douronensis (Roesma et al 2017), new record species of Puntius from West Sumatra (Roesma et al 2018), taxonomy confirmation of Puntius cf. binotatus in Gunung Tujuh Lake (Roesma et al 2019), and phylogenetic analysis of transparent gobies in three Sumatran Lakes (Roesma et al 2020).…”
Section: Introductionmentioning
confidence: 99%